정밀여과를 이용한 물재이용 공정의 산화전처리가 수질 및 막여과 성능에 미치는 영향 - 박재민(Jae Min Park); 이원태(Wontae Lee) (Daehan hwan'gyeong gonghag hoeji, 2020)
목적:본 연구는 막을 이용한 하수재이용 시설에서 오존, 이산화염소, 염소 전처리가 수질과 정밀여과 특성에 미치는 영향을 파악하였다. 방법:오존(0.5~2.5 mg/L), 이산화염소(1~5 mg/L), 염소(1~5 mg/L)를 정밀막여과(PVDF) 공정 전처리 산화제로 주입하고 수질 변화와 이에 따른 막오염 저감 및 막표면 손상을 평가하였다. 결과 및 토의:오존과 염소의 주입량이 증가할수록 소수성 물질의 분해가 증가하였으나 이산화염소는 본 실험에 사용된 주입량(1~5 mg/L) 범위에서 소수성 유기물을 잘 분해하지 못했다. 염소로 전처리한 경우 막 여과 운전시간이 오존과 이산화염소로 전처리한 경우에 비하여 길었다. 염소 주입농도(1~5 mg/L)가 증가할수록 역세척 전 막여과시간도 점차적으로 길어졌다. 산화제 종류 및 농도(오존 10 mg/L 이하, 이산화염소 20 mg/L 이하, 염소 40 mg/L 이하)에 관계없이 28일 이내는 산화제에 의한 막 손상률이 1% 이하였으며 막의 표면 손상도 발견되지 않았다. 결론:A하수처리장의 생물학적처리수를 재이용수로 활용하기 위해 PVDF 재질 막으로 정밀여과시 염소가 가장 효율적인 전처리 산화제로 판단된다. Objective:This study investigated the effects of ozone, chlorine dioxide, and chlorine pretreatment on water quality and microfiltration characteristics in the water reclamation facility. Methods:Ozone (0.5-2.5 mg/L), chlorine dioxide (1-5 mg/L) and chlorine (1-5 mg/L) were injected as an pre-oxidizing agent, and membrane fouling and surface damage during microfiltration (PVDF) were assessed. Results and Discussion:The hydrophobic substances were decomposed as the dosages of ozone and chlorine injected increased. However, chlorine dioxide could not effectively decompose hydrophobic organic matters in the range of 1-5 mg/L. In the case of pretreatment with chlorine, the microfiltration operation time was longer than in the case of pretreatment with ozone and chlorine dioxide. As the concentration of chlorine injection increased, the membrane filtration time before backwash gradually increased. Regardless of the type and concentration of the oxidizing agent, the membrane damage rate by the oxidizing agent was less than 1% within 28 days, and no surface damage was observed. Conclusions:Chlorine was considered to be the most efficient pre-oxidizer for microfiltration process with a PVDF membrane to reuse biologically treated wastewater in the wastewater treatment plant. KCI Citation Count: 0